Algebraic expressions for estimating the impact depths of a surface barrier over a homogeneous soil. Issue 1 (7th February 2020) - Zhang, Zhuanfang Fred
Abstract: Engineered surface barriers are used to isolate subsurface contaminants for effective long‐term containment of waste of a variety of types. The impact depths of a surface barrier are affected by the pre‐barrier recharge rate and the properties of the soil beneath the barrier. In this paper, algebraic expressions are developed to estimate drainage velocities and barrier impact depths after the emplacement of a surface barrier. Four impact depth terms are used to convey barrier impact: the near‐zero‐, 50%, average‐, and full‐impact depths. The algebraic expressions show that the average‐impact depth is no more than one‐third of the near‐zero‐impact depth, whereas the 50% impact depth is slightly larger than one‐half of the near‐zero‐impact depth. The full‐impact depth, depending on the final recharge rate from the surface barrier, is usually much smaller than the other impact depths. These differences lead to a very large transition zone beneath a surface barrier. A field drainage experiment and a series of numerical simulations were used to test the algebraic expressions. The experimental data and numerical results corroborated the analytical models by predicting very similar water content profiles and/or near‐zero‐, 50%, average‐, and full‐impact depths during the drainage process. The algebraic expressions provided are useful for quickly identifying sites where the depth of the existing contaminants could be beyond the protection of a surface barrier. Core Ideas: Algebraic expressions are developed to estimate barrier impact depths. The near‐zero‐, 50%, average‐, and full‐impact depths are defined. The experiment and numerical results corroborated the analytical models. The expressions are useful for identifying sites suitable for using surface barriers.